GENERALIZATION OF THE METHOD OF LINEAR INTEGRAL EQUATIONS HAVING FUNDAMENTAL SIGNIFICANCE FOR GRAVIMETRY AND MAGNETOMETRY: 4. FILTERING OF VECTORS IN THE RIGHT PARTS OF LINEAR ALGEBRAIC EQUATION SYSTEMS. CONCLUDING REMARKS - Strakhov V.N. (My University, 2004)
The paper is dedicated to two themes. The first (theme is the solution of the problem of filtering of data vector f δ The second theme is developing a principally new theory for regularization of linear algebraic equations system (LAESs)